Insulin in the Brain: There and Back Again - Banks, William A. (2012)
Insulin performs unique functions within the CNS. Produced nearly exclusively by the pancreas, insulin crosses the blood-brain barrier (BBB) using a saturable transporter, affecting feeding and cognition through CNS mechanisms largely independent of glucose utilization. Whereas peripheral insulin acts primarily as a metabolic regulatory hormone, CNS insulin has an array of effects on brain that may more closely resemble the actions of the ancestral insulin molecule. Brain endothelial cells (BEC), the cells that form the vascular BBB and contain the transporter that translocates insulin from blood to brain, is itself regulated by insulin. The insulin transporter is altered by physiological and pathological factors including hyperglycemia and the diabetic state. The latter can lead to BBB disruption. Pericytes, pluripotent cells in intimate contact with the BEC, protect the integrity of the BBB and its ability to transport insulin. Most of insulin’s known actions within the CNS are mediated through two canonical pathways, the phosphoinositide-3 kinase (PI3)/Akt and Ras/mitogen activated kinase (MAPK) cascades. Resistance to insulin action within the CNS, sometimes referred to as diabetes mellitus type III, is associated with peripheral insulin resistance, but it is possible that variable hormonal resistance syndromes exist so that resistance at one tissue bed may be independent of that at others. CNS insulin resistance is associated with Alzheimer’s disease, depression, and impaired baroreceptor gain in pregnancy. These aspects of CNS insulin action and the control of its entry by the BBB are likely only a small part of the story of insulin within the brain.